Disruption of cultural burning promotes shrub encroachment and unprecedented wildfires. Issue 5 (15th February 2022) - Mariani, Michela; Connor, Simon E; Theuerkauf, Martin; Herbert, Annika; Kuneš, Petr; Bowman, David; Fletcher, Michael‐Shawn; Head, Lesley; Kershaw, A Peter; Haberle, Simon G; Stevenson, Janelle; Adeleye, Matthew; et al.
Abstract : Recent catastrophic fires in Australia and North America have raised broad‐scale questions about how the cessation of Indigenous burning practices has impacted fuel accumulation and structure. For sustainable coexistence with fire, a better understanding of the ancient nexus between humans and flammable landscapes is needed. We used novel palaeoecological modeling and charcoal compilations to reassess evidence for changes in land cover and fire activity, focusing on southeast Australia before and after British colonization. Here, we provide what we believe is the first quantitative evidence that the region's forests and woodlands contained fewer shrubs and more grass before colonization. Changes in vegetation, fuel structures, and connectivity followed different trajectories in different vegetation types. The pattern is best explained by the disruption of Indigenous vegetation management caused by European settlement. Combined with climate‐change impacts on fire weather and drought, the widespread absence of Indigenous fire management practices likely preconditioned fire‐prone regions for wildfires of unprecedented extent.